Avocado oil encapsulation with OSA-esterified taro starch as wall material: Physicochemical and morphology characteristics. (March 2021) - Romero-Hernandez, Hector A.; Sánchez-Rivera, Mirna M.; Alvarez-Ramirez, Jose; Yee-Madeira, Hernani; Yañez-Fernandez, Jorge; Bello-Pérez, Luis A.
Abstract: The objective of the work was to evaluate OSA-esterified taro starch as wall material to encapsulate avocado oil as lipophilic bioactive compounds, using spray drying for encapsulation. It was found that OSA-esterification decreased the amylose content (8.93–6.13%), %C (33.29–31.88%), and thermal properties of gelatinization (Tp: 86.1 to 80.7 °C, and △H: 8.4 to 7.9 J g −1 ). Besides, OSA-esterification did not modify the diffraction pattern (Type A). The OSA-starch granules did not show surface alterations, while showing a monomodal particle diameter distribution. However, the particle diameter increased from 2.8 to 3.3 μm after modification. The emulsions of OSA-starch (350 and 400 mg starch. mL −1 oil) showed greater stability against coalescence than those obtained with unmodified starch. Encapsulates with native and OSA-starches showed differences in diameter, shape and presence of pores. Likewise, the esterification reduces the diameter distribution in the microcapsules (15.1–13.1 μm). The vegetable oil was located internally and superficially in the cavities and intraparticle area of the microcapsules. Encapsulation efficiency was increased by modification with OSA from 23.63 to 40.0% and the value of peroxides decreased during storage. The results demonstrated that malanga OSA-starch can be considered as wall material for protection of hydrophobic substance. Highlights: Encapsulates with OSA taro starch showed reduction in diameter compare with its native counterpart. Encapsulation efficiency of avocado oil increased with OSA taro starch. Avocado oil was present in the internally and superficially cavities and interparticle area. The core material showed low rancidity during storage.